Eagle syndrome: toward a clinical delimitation - González-García, N.; Porta-Etessam, J.; García-Azorín, D. (Neurología (Barcelona, English ed. ), 2021)
Orofacial and cervical pain are a frequent reason for neurology consultations and may be due to multiple pathological processes. These include Eagle syndrome (ES), a very rare entity whose origin is attributed to calcification of the stylohyoid ligament or elongation of the temporal styloid process. We present a series of five patients diagnosed with ES. We describe the demographic and clinical characteristics and response to treatment of 5 patients who attended the headache units of 2 tertiary hospitals for symptoms compatible with Eagle syndrome. The patients were 3 men and 2 women aged between 24 and 51, presenting dull, intense pain, predominantly in the inner ear and the ipsilateral tonsillar fossa. All patients had chronic, continuous pain in the temporal region, with exacerbations triggered by swallowing. Four patients had previously consulted several specialists at otorhinolaryngology departments; one had been prescribed antibiotics for suspected Eustachian tube inflammation. In all cases, the palpation of the tonsillar fossa was painful. Computed tomography scans revealed an elongation of the styloid process and/or calcification of the stylohyoid ligament in 3 patients. Four patients improved with neuromodulatory therapy (duloxetine, gabapentin, pregabalin) and only one required surgical excision of the styloid process. Eagle syndrome is a rare and possibly underdiagnosed cause of craniofacial pain. We present 5 new cases that exemplify both the symptoms and the potential treatments of this entity. El dolor orofacial y cervical es un motivo de consulta frecuente, que puede deberse a múltiples procesos patológicos. Entre ellos se encuentra el síndrome de Eagle, entidad muy infrecuente cuyo origen se atribuye a una osificación del ligamento estilohioideo o una elongación de la apófisis estiloides. Presentamos una serie de cinco pacientes con dicho diagnóstico. Se describen las características demográficas y clínicas de cinco pacientes atendidos en las Unidad de Cefaleas de dos hospitales terciarios por un cuadro compatible con síndrome de Eagle, y su respuesta a distintos tratamientos. Se trata de 3 varones y 2 mujeres, de entre 24 y 51 años, con dolor de localización predominante en un oído y la región amigdalina ipsilateral, de cualidad sorda y de gran intensidad. En todos ellos el patrón temporal era crónico y continuo, con exacerbaciones desencadenadas por la deglución. Cuatro pacientes habían realizado múltiples consultas en servicios de otorrinolaringología, y uno de ellos había recibido tratamiento antibiótico ante la sospecha de tubaritis. En todos los casos la palpación de la fosa amigdalina resultó dolorosa. En tres de los pacientes se demostró elongación de la apófisis estiloides y/o calcificación del ligamento estilohioideo mediante tomografía computarizada. Cuatro mejoraron con tratamiento neuromodulador (duloxetina, gabapentina, pregabalina) y sólo uno precisó cirugía con escisión de la apófisis estiloides. El síndrome de Eagle es una causa de dolor cráneo-facial poco frecuente, y posiblemente infradiagnosticada. Aportamos cinco nuevos casos que permiten delimitar tanto la semiología como los posibles tratamientos.